Forty Years of Development: Library Services at the College of The Bahamas - Walker, Berthamae L.; Ballance, Virginia C. (International Journal of Bahamian Studies, 2015)
From its establishment in 1974, administrators of the College of The Bahamas have taken the provision of library services seriously, realizing that any tertiary-level institution requires a strong library collection to assure its credibility as an academic institution. The library system of The College of The Bahamas consists of three libraries: the Harry C. Moore Library and Information Centre on the Oakes Field Campus, the Hilda Bowen Library on the Grosvenor Close Campus and the Northern Campus Library on the Freeport, Grand Bahama Campus as well as a small resource centre at the facility on Exuma. These libraries house collections of materials – books, journals, audio-visual resources and microfilm, as well as provide access to collections of electronic resources needed to support academic programs and research at the College. The Harry C. Moore Library and Information Centre also houses the Bahamian Special Collection, the College Archives as well as several special exhibition spaces.